Understanding past abrupt climatic change through the reduction of chronological uncertainty - Kearney, R (2020)
Across Europe, palaeoclimatic records dated to the Last Glacial-Interglacial Transition (LGIT; 16-8 cal. ka BP) provide evidence for several abrupt climatic oscillations on millennial and centennial-timescales. Understanding the spatial and temporal environmental response to these climatic events on a continental scale is important for providing insight into future climate scenarios. This relies on providing precise chronologies for palaeoenvironmental records, but issues with large dating uncertainties, and the practice of tuning/wiggle-matching different records together, has limited our ability to test for (a)synchroneity for abrupt climate transitions. In this study, the temporal and spatial complexity of LGIT climatic events, specifically, the Younger Dryas (YD) and earliest Holocene (EH) were investigated. Several of the most precisely dated pollen records were selected, spanning from northern to southern Europe. These sites were chosen using selection criteria that required independent chronologies based on radiocarbon dating and tephrochronology. To broaden the geographic range, a cryptotephra investigation was also undertaken on two palaeoenvironmental records from Romania (Lake Lia and Lake Brazi). Using Bayesian chronological modelling, each site’s ages and the widespread tephra layers were remodelled. Pollen records were also re-investigated using the statistical methods of Principal Curve analysis to assist in identifying abrupt climatic transitions. The INTIMATE Integration tool was utilised to enable quantified comparisons between these terrestrial sites and the high-resolution Greenland ice core records. The results from the Romanian cryptotephra investigation highlight the importance of this region to expand tephrostratigraphic frameworks across Europe, the Mediterranean and Anatolia. The identification of ultra-distal tephra layers allowed for a broader investigation into the timing of LGIT events. This study showed that even with the most precisely dated sites and, despite the methodological approaches employed here, identifying a clear time-transgression for the YD and centennial-scale events within the EH remains difficult due to chronological uncertainties. Issues with proxy and dating resolutions currently limit the chronological approach undertaken. Nonetheless, using widespread tephra layers and statistical methods on proxy records can help to evaluate the potential asynchrony of abrupt climate transitions and the possible climatic drivers. Overall, this study highlights the need to provide robust chronologies by undertaking high-resolution radiocarbon dating and proxy reconstruction, supplemented by tephrochronology. By employing these approaches with Bayesian age modelling, the temporal and spatial response to abrupt climatic shifts can be further explored.